REVIEW ARTICLE: ANALISIS FAKTOR KETIDAKPATUHAN MINUM OBAT HIPERTENSI PADA PASIEN HIPERTENSI - Elfia Neswita; Nurasni Nurasni; Efilia Meirita; Mandike Ginting (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2026)
Hypertension is one of the most common non-communicable disease (NCDs) worldwide. This condition has the potential to lead to serious complications such as stroke, heart disease, and kidney failure. Effective hypertension management involves regular use of antihypertensive medications. However, patient compliance with medication is still relatively low. This non-compliance can lead to suboptimal blood pressure control and increase the risk of complications. This systematic review aims to describe and analyze various factors influencing adherence to treatment in hypertensive patients. The results are expected to serve as evaluation material to help patients improve their medication adherence. The method used was aticle review. Selected article met the following criteria: published between 2020 and 2025, available in full-text form, and employed both qualitative and quantitative research designs. Following a selection process based on these criteria, relevant articles were further analyzed. Findings from 12 studies indicate that the factors most frequently influencing adherence are knowledge, education, motivation, and family support. Additionally, other factors such as occupation, distance from residence to healthcare facilities, the role of heathcare professionals, and perceptions of the disease also contribute to patient adherence. Therefore, patients are advised to be more proactive in increasing self-awareness and practicing self-care, thereby better managing their hypertension and preventing potential complications. The implication of this systematic review is that efforts to improve medication adherence among hypertensive patients must be multidisciplinary and comprehensive, involving patients, families, healthcare professionals, and healthcare services